Odpowiedzi

2010-02-03T09:36:22+01:00
A) { 3(x-½) + 2(y+3)= 3½
{ (3x - 1)/3 - (y + 3)/2 = -1|*6

3x-1,5+2y+6=3,5
6x-2-3y-9=-6

3x+2y+4,5=3,5|-4,5
6x-3y-11=-6|+11

3x+2y=-1|*(-2)
6x-3y=5

-6x-4y=2
6x-3y=5
-7y=7|:7

y=-1
3x-1,5-2-6=3,5|-2,5

y=-1
3x=1|:3

y=-1
x=1/3

b) { (x-3)/4 - (y + 5)/2 = -1,5|*8
{ (x-3)/2 - (2y-7)/3 = 1 |*6

2x-6-4y-20=-12|+26
3x-9-4y+14=6|-5

2x-4y=14
3x-4y=1|*(-1)

2x-4y=14
-3x+4y=-1
-x=13|*(-1)
x=-13

x=-13
-26-6-4y-20=-12

x=-13
-4y-52=-12|+52

x=-13
-4y=40|:(-4)

x=-13
y=-10

c) { (2x-5)/2 - (x-6y)/4 = (x+y)/2|*4
{ (3x-1)/10 + (2y-5)/5 =(2x+y)/2 |*10

4x-10-x+6y=2x+2y
3x-1-4y-10=10x+5y

3x+6y-10=2y+2x|+10
3x-4y-11=10x+5y|+11

3x+6y=2y+2x+10|-(2x+2y)
3x-4y=10x+5y+11|-(10x-5y)

x-2y=10
-7x+y=11|*(2)

x-2y=10
-14x+2y=22

-13x=32
















1 5 1
2010-02-03T10:34:02+01:00
1)
{ 3(x-½) + 2(y+3)= 3½
{ (3x - 1)/3 - (y + 3)/2 = -1 /*6

3x-1,5+2y+6=3,5
6x-2-3y-9=-6

3x+2y+4,5=3,5
6x-3y-11=-6

3x+2y=-1 /*(-2)
6x-3y=5

-6x-4y=2
6x-3y=5
______
y=-1
x=1/3

2)
{ (x-3)/4 - (y + 5)/2 = -1,5 /*8
{ (x-3)/2 - (2y-7)/3 = 1 / *6

2x-6-4y-20=-12
3x-9-4y+14=6

2x-4y=14
3x-4y=1 /*(-1)

2x-4y=14
-3x+4y=-1
_________
x=-13
y=-10

3)
{ (2x-5)/2 - (x-6y)/4 = (x+y)/2 /*4
{ (3x-1)/10 + (2y-5)/5 =(2x+y)/2 /*10

4x-10-x+6y=2x+2y
3x-1-4y-10=10x+5y

3x+6y=2y+2x+10
3x-4y=10x+5y+11

x-2y=10
-7x+y=11 /*2

x-2y=10
-14x+2y=22
______________
y=-32/13
x=26,6
1 5 1